Eksperimen Pembelajaran Matematika dengan Strategi Problem Posing dan Problem Based Learning terhadap Hasil Belajar ditinjau dari Tingkat Keaktifan pada Siswa Kelas VIII SMP Muhammadiyah 7 Surakarta - Aprilia, Asih, Prof. Dr. Sutama, M.Pd (2017)
This research three purposes. (1) examine the effect of learning strategies Problem Posing and Problem Based Learning toward mathematics learning outcomes, (2) examine the effect of the level of activity toward mathematics learning outcomes, (3) examine interaction between learning strategies and the level of activity toward mathematics learning outcomes. The type of this research is quantitative with quasi-experimental design. The population in this research is all students of VIII SMP Muhammadiyah 7 Surakarta of academic year 2016/2017. Sample of this research consisted of two classes there are experiment class and control class with the sampling technique using cluster random sampling. Methods of data collection used documentation, questionnaire, and test. Techniques of analyzed used analysis of variance two paths with different cell with a significance level of 5%. Results of the data analysis was obtained: (1) there is a effect between Problem Posing and Problem Based Learning strategies toward mathematics learning outcomes, (2) there is a effect level of activity toward mathematics learning outcomes, and (3) there is no interaction between the learning strategies and level of activity toward mathematics learning outcomes. Keywords: level of activity, mathematics learning outcomes, problem based learning, problem posing